Transoral Robotic Surgery and the Unknown Primary: A Cost-Effectiveness Analysis - Byrd, J Kenneth; Smith, Kenneth J; de Almeida, John R; Albergotti, W Greer; Davis, Kara S; Kim, Seungwon W; Johnson, Jonas T; Ferris, Robert L; Duvvuri, Umamaheswar (Otolaryngology-head and neck surgery, 2014)
To evaluate the cost-effectiveness of transoral robotic surgery (TORS) for the diagnosis and treatment of cervical unknown primary squamous cell carcinoma (CUP). Case series with chart review. Tertiary academic hospital. A retrospective chart review was performed on patients with new occult primary squamous cell carcinoma of the head and neck with nondiagnostic imaging and/or endoscopy who were treated with TORS at a tertiary hospital between 2009 and 2012. Direct costs were obtained from the hospital's billing system, and national data were used for inpatient hospital costs and physician fees. The proportion of tumors found in 3 strategies was used as effectiveness to calculate the incremental cost-effectiveness ratio. In total, 206 head and neck robotic cases were performed at our institution between December 2009 and December 2012. Three surgeons performed TORS on 22 patients for occult primary squamous cell carcinoma. The primary tumor was located in 19 of 22 patients (86.4%). The incremental cost-effectiveness ratio for sequential and simultaneous examination under anesthesia with tonsillectomy (EUA) and TORS base of tongue resection was $8619 and $5774 per additional primary identified, respectively. Sequential EUA followed by TORS is associated with an incremental cost-effectiveness ratio of $8619 compared with traditional EUA alone. Bilateral base of tongue resection should be considered in the workup of these patients, particularly if the palatine tonsils have already been removed.